PYK2 via S6K1 regulates the function of androgen receptors and the growth of prostate cancer cells. Issue 8 (August 2016) - Hsiao, Yu-Hsuan; Huang, Yu-Ting; Hung, Chia-Yu; Kuo, Tzu-Chien; Luo, Fuh-Jinn; Yuan, Ta-Chun
Abstract : Androgen receptor (AR) is a steroid hormone receptor that functions as a transcription factor for regulating cell growth and survival. Aberrant AR function becomes a risk factor for promoting the progression of prostate cancer (PCa). In this study, we examined the roles of proline-rich tyrosine kinase 2 (PYK2) and ribosomal S6 kinase 1 (S6K1) in regulating AR expression and activity and growth properties in PCa cells. Compared with normal prostate tissues, PCa tumors exhibited high levels of PYK2 and S6K1 expression. Furthermore, the expression levels of PYK2 and S6K1 were significantly correlated with nuclear AR expression in PCa tissues. We further found the association between PYK2, S6K1, and AR in their protein expression and phosphorylation levels among normal prostate PZ-HPV-7 cells and prostate cancer LNCaP and 22Rv1 cells. Overexpression of the wild-type PYK2 in PZ-HPV-7 and LNCaP cells promoted AR and S6K1 expression and phosphorylation as well as enhanced cell growth. In contrast, expression of the mutated PYK2 or knockdown of PYK2 expression in LNCaP or 22Rv1 cells caused reduced expression or phosphorylation of AR and S6K1 as well as retarded cell growth. Under an androgen-deprived condition, PYK2-promoted AR expression and phosphorylation and PSA production in LNCaP cells can be abolished by knocking down S6K1 expression. In summary, our data suggested that PYK2 via S6K1 activation modulated AR function and growth properties in PCa cells. Thus, PYK2 and S6K1 may potentially serve as therapeutic targets for PCa treatment.